Improving MSME Credit Access through Standardization of Financial Statements: A Study in Banten Province - Rahayu Kusumawati (Jurnal Pengabdian Pancasila (JPP), 2025)
The Republic of Indonesia Government Regulation Number 23 of 2018 concerning Income Tax on Income from Businesses Received or Obtained by Taxpayers Who Have a Certain Gross Turnover mandates Micro, Small, and Medium Enterprises (MSMEs) to prepare financial reports according to applicable standards within the latest time. 7 years. On the other hand, there is a quite crucial problem for the majority of MSMEs in South Tangerang City, namely the lack of knowledge capacity regarding preparing financial reports. This of course will be an inhibiting factor for them. The absence of adequate financial reports will be an obstacle for MSMEs in obtaining loans from financing institutions, and can also threaten the financial position of MSMEs themselves. Based on requests from the Small and Medium Enterprises Cooperatives Service for requests for training and assistance in preparing financial reports, the PKN STAN Community Service team plans to provide training and assistance in preparing financial reports for MSMEs under the auspices of the relevant Department in collaboration with Bank Indonesia, as SI APIK application owner. The output target of this community service activity is the realization of MSME financial reports using Android and Web-based applications, namely the SI APIK application, so it is hoped that these financial reports can be "bankable" in terms of obtaining loans from financial institutions.